Search for the lepton-flavor-violating decays B0s → e±μ∓ and B0 → e±μ∓ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
A search for the lepton-flavor-violating decays B0s→e±μ∓ and B0→e±μ∓ is performed with a data sample, corresponding to an integrated luminosity of 1.0 fb−1 of pp collisions at √s=7 TeV, collected by the LHCb experiment. The observed number of B0s→e±μ∓ and B0→e±μ∓ candidates is consistent with background expectations. Upper limits on the branching fractions of both decays are determined to be B(B0s→e±μ∓)<1.1(1.4)×10−8 and B(B0→e±μ∓)<2.8(3.7)×10−9 at 90% (95%) confidence level (C.L.). These limits are a factor of 20 lower than those set by previous experiments. Lower bounds on the Pati-Salam leptoquark masses are also calculated, MLQ(B0s→e±μ∓)>101 TeV/c2 and MLQ(B0→e±μ∓)>126 TeV/c2 at 95% C.L., and are a factor of 2 higher than the previous bounds.
Im Titel sind "0", "±" und "∓" hochgestellt und "s" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 615
Gesehen am 23.04.2021